Iron Fist in a Velvet Glove: Class IV Ferroptosis Inducers as a Novel Strategy to Target Ovarian Cancer - Lavinia Petriaggi; Emanuele Giorgio; Giuseppe Natali; Cristiana Galeano; Simão Rodrigues Furtado; Concetta Maria Faniello; Francesco Saverio Costanzo; Flavia Biamonte; Anna Martina Battaglia (Frontiers in Bioscience-Landmark)
Epithelial ovarian cancer (EOC) is a highly lethal gynecological malignancy characterized by frequent late-stage diagnosis, high rates of chemoresistance, and poor long-term survival. Emerging evidence underscores the central role of iron metabolism dysregulation in EOC pathogenesis, progression, and treatment resistance. Ovarian cancer cells and cancer stem cells exhibit an “iron-addicted” phenotype, characterized by increased iron uptake, reduced export, and enhanced storage, which sustains proliferative signaling, redox imbalance, and metastatic potential. Recent advances have illuminated ferroptosis, a regulated form of iron-dependent cell death driven by lipid peroxidation, as a promising therapeutic target for overcoming resistance to platinum-based chemotherapy. This review provides a comprehensive synthesis of the mechanisms governing iron metabolism and ferroptosis in EOC, with a particular focus on Class IV ferroptosis inducers (FINs). These agents act by disrupting iron homeostasis and promoting labile iron pool accumulation, thereby triggering oxidative stress and ferroptotic death. Preclinical studies demonstrate that Class IV FINs, including iron nitroprusside, superparamagnetic iron oxide nanoparticles, ferric ammonium citrate, and Ferlixit, exhibit potent antitumor activity in EOC models, particularly in chemoresistant and stem-like tumor subpopulations. Furthermore, Class IV FINs show synergistic effects when combined with other ferroptosis modulators or immunotherapeutic agents. Despite their promise, clinical translation remains limited by challenges in bioavailability, delivery specificity, and potential systemic toxicity. Ongoing efforts in nanotechnology, biomarker discovery, and tumor stratification offer new avenues for refining ferroptosis-based interventions. Ultimately, this review highlights Class IV FINs as a mechanistically distinct and clinically actionable strategy to target metabolic vulnerabilities in EOC, with the potential to reshape therapeutic paradigms and improve patient outcomes.